The neural correlates of grandmaternal caregiving. Issue 1963 (24th November 2021) - Rilling, James K.; Gonzalez, Amber; Lee, Minwoo
Abstract : In many societies, grandmothers are important caregivers, and grandmaternal investment is often associated with improved grandchild well-being. Here, we present, to our knowledge, the first study to examine grandmaternal brain function. We recruited 50 grandmothers with at least one biological grandchild between 3 and 12 years old. Brain function was measured with functional magnetic resonance imaging as grandmothers viewed pictures of their grandchild, an unknown child, the same-sex parent of the grandchild, and an unknown adult. Grandmothers also completed questionnaires to measure their degree of involvement with and attachment to their grandchild. After controlling for age and familiarity of stimuli, viewing grandchild pictures activated areas involved with emotional empathy (insula and secondary somatosensory cortex) and movement (motor cortex and supplementary motor area). Grandmothers who more strongly activated areas involved with cognitive empathy (temporo-parietal junction and dorsomedial prefrontal cortex) when viewing pictures of the grandchild desired greater involvement in caring for the grandchild. Finally, compared with results from an earlier study of fathers, grandmothers more strongly activated regions involved with emotional empathy (dorsal anterior cingulate cortex, insula and secondary somatosensory cortex), and motivation (nucleus accumbens, ventral pallidum and caudate nucleus). All in all, our findings suggest that emotional empathy may be a key component of grandmaternal responses to their grandchildren.